2019
DOI: 10.1007/s13187-019-01494-6
|View full text |Cite
|
Sign up to set email alerts
|

How Cancer Patients Perceive Clinical Trials (CTs) in the Era of CTs: Current Perception and Its Differences Between Common and Rare Cancers

Abstract: Background: As perception have been recently highlighted as critical determinants of clinical trials (CTs) in cancer patients, we evaluated current perceptional status of CTs in cancer patients, focusing on differences between common and rare cancers. Materials & Methods:From November 2015 to May 2017, we prospectively surveyed patients who have received anti-cancer treatment at Asan Medical Center using the PARTAKE questionnaires.Results: Among 333 respondents, 70.9% and 29.1% had common and rare cancers, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…25 Psychosocial barriers to trial participation may also exist. Park and colleagues 26 found patients receiving treatment for both common and rare cancers expressed fear, safety concerns, and lacked knowledge surrounding clinical trial benefits. Kotowski et al 27 investigated how patient willingness to participate in clinical trials relates to their familiarity with trials.…”
Section: Discussionmentioning
confidence: 99%
“…25 Psychosocial barriers to trial participation may also exist. Park and colleagues 26 found patients receiving treatment for both common and rare cancers expressed fear, safety concerns, and lacked knowledge surrounding clinical trial benefits. Kotowski et al 27 investigated how patient willingness to participate in clinical trials relates to their familiarity with trials.…”
Section: Discussionmentioning
confidence: 99%
“…7 This is certainly the case for rare cancers such as sarcomas, where patient numbers are so small that it is challenging to conduct a RCT within a realistic timeframe with a manageable number of collaborators and statistical power (Table 1). [10][11][12] Furthermore, as our knowledge of biologic diversity within histologic subtypes of sarcomas advances, there is a trend toward more studies concentrating on molecular targets, increasing RCT complexity. 13 Current guidelines recommend multidisciplinary care at specialized centers, for localized tumors often requiring extensive surgical excision and (neo)adjuvant radiotherapy (RT) for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the under-representation of such groups and promoting inclusion is important to have more accurate and representative outcomes and expand access to new cancer treatments. Moreover, one recent study found that patients with rare cancers are significantly less willing to participate in clinical trials compared to patients with common cancers (17). Despite the challenges, clinical trials on common and rare gynecological cancers have advanced in investigating targeted therapies including antiangiogenic agents, PARP inhibitors, tumor-intrinsic signaling pathway inhibitors, selective estrogen receptor down-regulators, and immune checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%